Analisis Sekuestrasi Karbon dan Stok Karbon pada Hutan Mangrove di Desa Waworaha, Kecamatan Soropia, Kabupaten Konawe - Indriyani, Lies; Kahirun, Kahirun; Erif, La Ode Muhammad (MAKILA, 2025)
Mangrove ecosystems play a strategic role in global climate change mitigation due to their capacity to sequester and store carbon. This study aims to analyse carbon sequestration and carbon stocks in the mangrove forests of Waworaha Village, Soropia District, Konawe Regency. The research was conducted in February 2025 using a non-destructive sampling approach combined with established allometric equations to estimate aboveground biomass, with carbon content assumed to be 50% of the total biomass. Seven plots measuring 20 m × 20 m were purposively established based on mangrove zonation and substrate characteristics. Diameter at breast height (DBH) was measured for trees ≥10 cm, and data were analysed descriptively to quantify biomass variation across species and plots. The results indicate that mean biomass, carbon sequestration, and carbon stock values reached 174.76 tons/ha, 295.05 tons CO₂/ha, and 80.38 tons C/ha, respectively. Among recorded species, Sonneratia alba exhibited the highest carbon values, while Rhizophora apiculata contributed the lowest, reflecting significant interspecific variation influenced by morphological traits, density, and environmental conditions. Spatial variability across plots suggests the influence of tidal inundation frequency, nutrient availability, and substrate stability on biomass accumulation. These findings underscore the ecological significance of mangrove forests in storing blue carbon and their contribution to Indonesia’s Nationally Determined Contribution (NDC). The study recommends targeted rehabilitation in low-density plots, prioritising high-biomass species to enhance carbon uptake. Further research integrating soil carbon pools is essential to generate comprehensive carbon estimates for sustainable mangrove management.